ANALISIS PENGARUH FINANCIAL TARGET DAN EFFECTIVEMONITORING TERHADAP POTENSI KECURANGAN LAPORANKEUANGAN - Hamida, Hasna Marwa; Wilestari, Median; Efrinal (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study aims to analyze and determine the influence of financial targets and effectivemonitoring on the potential for financial statement fraud in companies in the metal and mineralsub-sector for the period 2020-2023. The research sample consisted of 13 companies in the metaland mineral sub-sector listed on the Indonesia Stock Exchange for the period 2020-2023, selectedusing purposive sampling with specific criteria. The data source used secondary data from theofficial website www.idx.co.id. The data analysis method used in this study was logistic regressionanalysis with the assistance of SPSS 23 statistical software. The results of this study indicate thatfinancial targets have a positive and significant influence on the potential for financial statementfraud. Effective monitoring has a positive but insignificant influence on the potential for financialstatement fraud.